2011
DOI: 10.1167/iovs.09-4686
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity Development of Children with Infantile Nystagmus Syndrome

Abstract: The pattern of visual acuity development differs among children with INS, depending on the presence or absence of associated sensory system deficits. Careful characterization of visual system differences in patients with INS is important if visual acuity is an outcome in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
0
25
1
8
Order By: Relevance
“…1 Visual acuity in patients with infantile nystagmus is limited by associated sensory deficits and amblyopia as well as an inability to maintain stable foveal fixation. 2 The results of previous studies of patients with bilateral infantile cataracts have suggested that the onset of preoperative manifest nystagmus portends a poor final visual outcome. 3,4 In one series of 24 infants who underwent surgery before 41 weeks of age, only 1 patient with preoperative nystagmus achieved a final visual acuity .20/200, whereas 5 patients had acuities ranging from 20/200 to 5/400.…”
mentioning
confidence: 99%
“…1 Visual acuity in patients with infantile nystagmus is limited by associated sensory deficits and amblyopia as well as an inability to maintain stable foveal fixation. 2 The results of previous studies of patients with bilateral infantile cataracts have suggested that the onset of preoperative manifest nystagmus portends a poor final visual outcome. 3,4 In one series of 24 infants who underwent surgery before 41 weeks of age, only 1 patient with preoperative nystagmus achieved a final visual acuity .20/200, whereas 5 patients had acuities ranging from 20/200 to 5/400.…”
mentioning
confidence: 99%
“…Insgesamt sind angeborene Anomalien des Sehnervenkopfes und des Sehnervs selten, können aber gerade bei beidseitigem Auftreten die visuelle Entwicklung nachhaltig beeinträchtigen [1,2,3,4,5].…”
Section: Beurteilungskriterien Von Papillenanomalienunclassified
“…Noch vor 30 Jahren waren Diagnosen wie die kongenitale Kata rakt oder der Buphthalmus die Erkrankungen, die zu Sehbehinderung im Kindesalter führten. In den Schulen für Sehbehinderte fanden sich überwiegend sonst gesunde Kinder [3,4,6,12].…”
Section: Angeborene Optikusatrophieunclassified
“…Poor color vision in infants may to some extent; however, be secondary to reduced contrast sensitivity [19]. Psychophysical studies to evaluate visual acuity maturation longitudinally suggest that patients with foveal hypoplasia exhibited visual improvement at the same rate as normative groups (during 2-4 years of age) [21]; after this time the visual acuity remains poor throughout the rest of their lives. However, this was a very small study and needs further investigation with larger cohorts of patients.…”
Section: Clinical Perspectivementioning
confidence: 99%